Search for down-type fourth generation quarks with the ATLAS detector in events with one lepton and hadronically decaying W bosons - Anduaga, Xabier Sebastián (2012)
This Letter presents a search for pair production of heavy down-type quarks decaying via b ′→Wt in the lepton+jets channel, as b′b' ̄′→W¯tW +t̄→bb̄W +W¯W +W¯ -→l ±νbb̄qq̄qq̄qq̄. In addition to requiring exactly one lepton, large missing transverse momentum, and at least six jets, the invariant mass of nearby jet pairs is used to identify high transverse momentum W bosons. In data corresponding to an integrated luminosity of 1.04fb -1 from pp collisions at √s=7TeV recorded with the ATLAS detector, a heavy down-type quark with mass less than 480GeV can be excluded at the 95% confidence level.